BOOK HISTORY IN FINLAND FROM THE 18TH CENTURY UNTIL TODAY - LAINE, TUIJA (Knygotyra, 2013)
In this paper, I shall introduce the research of book history in Finland during the last 300 years. How has book science developed from the eighteenth century onwards, what have been the main themes, and for what specific reasons have they become of central importance in the different periods of book history? And, last but not least, what methods have scholars used in book historical research?